Gender disparity in career mobility in urban China: a study on the barriers in the women's career development in harbin, the capital of Heilongjiang Province - Wang, Weihua (2007)
Although with the word's economy development, the society evolves, and the basic education improves, more and more female workers enter the job market have created a trend, the proportion of female top managers is uncoordinated. When women became important human resources, equal working rights emerges as an important issue. In China's organization, the high level position has less females comparing to the lower positions. This paper analyzes gender disparity in career mobility in Urban China. This search, taking the female executive leaders and male managers as the subjects, is aiming to understand the sexual discrimination difference of the superiors, and understand the different perceptions of Glass Ceiling of employees. The data used in this study contains a cross section of urban residents from the Women managers' directory in Heilongjiang province of China, and sample of male managers. The investigation intends to shed light on the following questions: 1) what is the pattern of gender differences in career mobility in Urban China? 2) What are the main determinants of gender disparity in career mobility? Multiple regression analysis is estimated. The empirical result shows that gender disparity is not associated with gender differences in human capital endowment, instead, Glass Ceiling, male stereotyping, family commitment, and women's negative attitude have significant negative effects on women's upward and downward career mobility.